Does Vitamin K Intake Influence High Phosphate Induced Vascular Pseudo-ossification: An Underappreciated Therapeutic Prospect in General Population? - Thent, Zar Chi; Fromming, Gabriele Ruth Anisah; Abd Muid, Suhaila (Researchgate, 2019)
Increasing interest on vascular pseudo-ossification has alarmed the modern atherosclerotic society. High phosphate is one of the key factors in vascular pseudo ossification, also known as vascular calcification. The active process of deposition of the phosphate crystals in vascular tissues results in arterial stiffness. High phosphate condition is mainly observed in chronic kidney disease patients. However, prolong exposure with high phosphate enriched foods such as canned drinks, dietary foods, etc. can be considered as modifiable risk factors for vascular complication in population with regardless of chronic kidney disease. High intake of vitamin K regulates the vascular calcification by exerting its anti-calcification effect. The changes in serum phosphate and vitamin K levels in normal individual with high phosphate intake are not well-investigated. This review summarised the underlying mechanisms of high phosphate induced vascular pseudo ossification such as vascular transdifferentiation, vascular apoptosis and phosphate uptake by sodium dependent co-transporters. Pubmed, Science Direct, Scopus, ISI Web of Knowledge and Google scholar were searched using the terms 'vitamin K', 'vascular calcification, 'phosphate', 'transdifferentiation' and 'vascular pseudo-ossification'. Vitamin K certainly activates the matrix GIA protein and inhibits vascular transition and apoptosis in vascular pseudo-ossification. The present view highlighted the possible therapeutic linkage between vitamin K and the disease. Understanding the role of vitamin K will be considered as potent prophylaxis agent against the vascular disease in near future.